Le lexique-grammaire de noms sous-spécifiés - Éric Laporte; Christiane Marque-Pucheu; Takuya Nakamura (Corela)
Underspecified nouns (Nss), those that can appear in a specificational construction (1) of the form Leur ambition a été d’innover “Their ambition was to innovate”, are often also predicates governing arguments in an elementary sentence (2) of the form Ils ont eu l’ambition d’innover “They had the ambition to innovate”, where Nss is the predicate accompanied by a support verb and its arguments N0 and N1. We studied nouns entering in both constructions (1) and (2) with the same meaning, and found three situations. With nouns such as ambition, (1) and (2) have almost the same meaning. With other entries, such as souvenir “memory” and preuve “proof”, the two constructions are not equivalent: the sentential predicative of (1) is absent from (2), whereas the N1 argument of (2) can appear as a prepositional complement of Nss in (1), and often (as with souvenir) specifies the theme of the content of the sentential predicative of (1). Finally, nouns such as embarras “embarrassment” are not typical Nss because the sentential predicative of (1) has a causal role; it has not the same content as N1. Thus, in the mémoire/preuve and embarras types, (1) seems to involve several elementary sentences.